Molecular approach to tooth decays [Diş çürüklerinin oluşumuna moleküler yaklaşım] - (:unkn) unknown (Halic Universitesi Fen-Edebiyat Fakultesi, 2010)
One of the greatest achievements of humankind in science is the near completion of the draft of the Human Genome Project in 2001. Information gained from this draft is now used to develop new molecular biological techniques used by oral health professionals. Although dental caries are considered to be an infectious disease, there are some genetic determinants for both the microorganisms and the host that causes susceptibility to dental decays. Studies including the monozygotic and dizygotic twins pioneered the genetic studies in understanding the genetic nature of tooth decays. As the outcomes of human genome project are started to be applied in the oral medicine, many researchers studied genes and their protein products that may contribute to tooth decay. The studied genes include HLA genes, AMELX, CD14, vitamin D receptor genes and genes that code for saliva components. Although some researchers correlate some polymorphisms and dental caries in small study groups, molecular markers that indicate increased risk or protection against dental caries have not been identified. Clinicians will hold more effective and preventive therapies whenever genetic factors contributing to carries risk and protection factors are identified.
Keywords: Carbonic anhydrase VI; Genetics; MUC7; Tooth decays; Vitamin D Receptor